TREATMENT OF A TEXTILE WASTEWATER USING AN ELECTROCOAGULATION REACTOR POWERED BY PHOTOVOLTAIC SOLAR ENERGY - Edson Alves De Jesus; Janaina Moreira Meneses; Marcos Alexandre Cavalcante de Araújo; Martin Lindsey Christoffersen (Environmental Smoke, 2021)
The textil industry uses a variety of dyes in the stage of coloring. The liquid effluent resulting at the end of the process has high turbidity and a large chemical oxygen demand. If these byproducts are dumped into natural water bodies, even in small quantities, they may produce damage to the aquatic environment and to human health. Electrocoagulation is becoming an efficient technique for the removal of pollutants from industrial effluents, it is easy to operate, and produces little sludge at the end of the treatment. In the present study, the use of an electrocoagulation reactor with aluminum electrodes proved efficient for turbidity removal from synthetic industrial effluents. The use of a solar plate of photovoltaic electricity for the functioning of the reactor was evaluated. Ideal time of treatment was 20 minutes. The use of a conventional energy source removed 63% of the turbidity. Using the voltaic solar energy source, a removal of 72% of turbidity was attained. We conclude that it is possible to use the alternative solar energy source in order to minimize costs resulting from electrical energy consumption, and, at the same time, to obtain the best results in the removal of pollutants.